INTRODUCTION TO MICROCONTROLLER AND PLC TO IMPROVE MINIMAL COMPETENCY ASSESSMENT LOGIC ABILITY STUDENTS OF SMAN 1 LUMAJANG - Imam Sutrisno; Isa Rachman; Rini Indarti; Irma Rustini; Edy Prasetyo Hidayat; Trisnowati Rahayu (Universitas Pahlawan Tuanku Tambusai, 2023)
The Minimum Competency Assessment is one of the national assessments used in 2021 by the Ministry of Education and Culture to replace the high school level national exam. It focuses on measuring literacy and numeric skills through students' logical abilities and reading comprehension. To trigger an increase in logic skills, SMAN 1 Lumajang students are given additional knowledge outside the curriculum. One of them is through the introduction of microcontrollers and PLCs, namely logic-based programming devices. This activity is also able to increase digital, technological and human literacy competencies in the era of the industrial revolution 4.0 because Microcontrollers and PLCs are widely used in the field of industrial automation. From the implementation of the activity it is known that the results of the participants' quizzes on each subject matter showed very satisfactory results with an average score of 76 and the results of the participants' tests at the end of the lesson also showed satisfactory results with an average score. out of 74. In addition, the results of the participant questionnaire in response to the implementation of the activity showed very good results. With these activities, the microcontroller and PLC can be used as one of the extracurricular activities to improve the competence of SMAN 1 Lumajang students.